2008
DOI: 10.1253/circj.cj-08-0328
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Left Ventricular Reconstructive Surgery in Patients With Ischemic Dilated Cardiomyopathy

Abstract: urgical treatment of congestive heart failure associated with myocardial infarction (MI) is attracting much attention because its prognosis is still poor despite recent improvements in medical treatment. 1 Post-MI left ventricular (LV) remodeling is characterized by chamber dilatation and abnormal geometric change, which leads to heart failure progressing to ischemic cardiomyopathy. Heart transplantation is widely accepted as the optimal surgical therapy for heart failure patients, including those associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The Osaka Cardiovascular Surgery Research (OSCAR) group observed signifi cant decreases in LVEDD and LVESD with increased LVEF postoperatively [9]. These LV functional improvements persisted for 3 years.…”
Section: Changes In Haemodynamic and Cardiac Variables After Svrmentioning
confidence: 99%
“…The Osaka Cardiovascular Surgery Research (OSCAR) group observed signifi cant decreases in LVEDD and LVESD with increased LVEF postoperatively [9]. These LV functional improvements persisted for 3 years.…”
Section: Changes In Haemodynamic and Cardiac Variables After Svrmentioning
confidence: 99%
“…Mean age was 32.8±17.8 years (range, 7-69 years) and the diagnosis was DCM in 20 patients, ischemic cardiomyopathy in 9, secondary cardiomyopathy in 3, and myocarditis in 2. Our protocol for scheduled LVAS weaning is shown in Figure. To facilitate future LVAS explantation, adjunctive operative procedures such as mitral annuloplasty (n=17), LV pacing lead implantation for cardiac resynchronization therapy (CRT) (n=5) or LV restoration (n=4) 39 were performed at the time of LVAS implantation if indicated. As soon as the patient's general condition was stabilized and organ dysfunction recovered, medical treatment for HF was instituted.…”
Section: Osaka University Experiencementioning
confidence: 99%
“…Mean EF significantly improved to 39±11%, and after a mean of 3.3±2.4 years of follow-up, 90% of the survivors were in NYHA functional class I or II. 35 In patients with ischemia, the prognosis is associated with the presence of more than moderate MR. 36 In ischemic DCM, the operative results are different with and without ischemic MR. In patients with MR, the preoperative status is severe and operative mortality seems to be high because of the severity of the disease and requirement for emergency operation.…”
Section: Left Ventricular (Lv) Restoration and Ischemic Cardiomyopathmentioning
confidence: 99%